The Power of a Bad Example - A Field Experiment in Household Garbage Disposal - Robert Dur; Ben Vollaard (Center for Economic Studies and ifo Institute (CESifo), 2014)
Field-experimental studies have shown that people litter more in more littered environments. Inspired by these findings, many cities around the world have adopted policies to quickly remove litter. While such policies may prevent people from following the bad example of litterers, they may also invite free-riding on public cleaning services. We are the first to show that both forces are at play. We conduct a natural field experiment where, in a randomly assigned part of a residential area, the frequency of cleaning was drastically reduced during a three-month period. We find evidence that some people start to clean up after themselves when public cleaning services are diminished. However, the tendency to litter more dominates. We also find that these responses continue to exist for some time after the treatment has ended.
Keywords: C93; H40; K42; 330; littering; public services; free-riding; field experiment